20‐4: High‐efficiency Perovskite QLED Achieving BT.2020 Green Chromaticity. Issue 1 (May 2017) - Hirose, Tomoya; Tsunoi, Toshiaki; Aoyama, Eriko; Ishigaki, Ayumi; Suzuki, Tsunenori; Inoue, Hideko; Nakashima, Harue; Seo, Satoshi; Tsutsui, Tetsuo
Abstract : A green perovskite‐quantum‐dot (Per‐QD) light‐emitting diode with high efficiency and color purity was fabricated. This device exhibited a narrow spectrum with a half width of 19 nm and covered the BT.2020 color gamut. Improving an electron‐transport layer increased the external quantum efficiency to 6.2%.